'It's a cultural thing': excuses used by health professionals on providing inclusive care. Issue 1 (2nd January 2022) - Mohamed Shaburdin, Zubaidah; Bourke, Lisa; Mitchell, Olivia; Newman, Trudie
ABSTRACT: Although health services in Australia have an aim to provide inclusive care for their patients/clients, this study highlights how barriers to care can lie at the centre of patient-provider interactions. Racial microaggression is a subtle form of racism that can occur in health settings, leading to further exclusion for First Nations Australians, immigrants and refugees. This paper is guided by Derrida's approach to deconstructionism by unpacking how language is used by health professionals – as holders of organisational power – and how they construct 'truths' or discourses about clients that historically have been marginalised by health services and system. Data comprise 21 interviews with staff from two rural health services. It identified three racial microaggressions were used to justify the challenges of providing care to people from First Nations, immigrant and refugee backgrounds: (1) Participants problematised culture(s) of service users; (2) participants implied cultural superiority in their conceptualisation of 'other' cultures; and (3) participants shared stories of inactions, discomfort and relegating of responsibility. The findings identified these discourses as forms of racial microaggression that can potentially lead to further exclusion of people seeking services and support.